Design Support Needs to Realize More Effective and Resource-Efficient Offerings: A Comparison Among Large Companies and Small and Medium Enterprises - Brambila-Macias, Sergio A.; Sakao, Tomohiko (Frontiers in Sustainability, 2021)
In an economic paradigm where companies think that more is better and resources are considered infinite, waste, pollution, and environmental degradation are often the result. This can, in turn, be addressed by companies focusing on offerings that are both effective and resource efficient. However, this type of offerings can be more uncertain and complex due to multiple factors such as multiple actors and conflicting objectives taking place at once. Large and small companies could benefit from dedicated design support to successfully realize these types of offerings. However, the type of support they might need is not clear. Differences and similarities among companies could guide researchers in providing more reliable support. Therefore, the aim of this research is to present differences and similarities of design support needs among large companies and small and medium enterprises. This is carried out through semi-structured interviews and follow-up meetings. The results show that differences include a formal product realization process for large companies and an informal or no process for smaller ones. Similarities point at design support for better communication and management of their offerings with regard to lead time as well as lifecycle and strategic thinking for decision making. The conclusions highlight the importance for researchers to provide design support that purposefully addresses specific needs.